Effects of exercise intensity and duration on nocturnal heart rate variability and sleep quality - Myllymäki, T.; Rusko, H.; Syväoja, H.; Juuti, T.; Marja-Liisa Kinnunen, M.-L.; Kyröläinen, H. (European Journal of Applied Physiology, 2012)
Acute physical exercise may affect cardiac autonomic modulation hours or even days during the recovery phase. Although sleep is an essential recovery period, the information on nocturnal autonomic modulation indicated by heart rate variability (HRV) after different exercises is mostly lacking. Therefore, this study investigated the effects of exercise intensity and duration on nocturnal HR, HRV, HR, and HRV-based relaxation, as well as on actigraphic and subjective sleep quality. Fourteen healthy male subjects (age 36 ± 4 years, maximal oxygen uptake 49 ± 4 ml/kg/min) performed five different running exercises on separate occasions starting at 6 p.m. with HR guidance at home. The effect of intensity was studied with 30 min of exercises at intensities corresponding to HR level at 45% (easy), 60% (moderate) and 75% (vigorous) of their maximal oxygen uptake. The effect of duration was studied with 30, 60, and 90 min of moderate exercises. Increased exercise intensity elevated nocturnal HR compared to control day (p < 0.001), but it did not affect nocturnal HRV. Nocturnal HR was greater after the day with 90- than 30- or 60-min exercises (p < 0.01) or control day (p < 0.001). Nocturnal HRV was lower after the 90-min exercise day compared to control day (p < 0.01). Neither exercise intensity nor duration had any impact on actigraphic or subjective sleep quality. The results suggest that increased exercise intensity and/or duration cause delayed recovery of nocturnal cardiac autonomic modulation, although long exercise duration was needed to induce changes in nocturnal HRV. Increased exercise intensity or duration does not seem to disrupt sleep quality.